(untitled) (Research, Society and Development, 2020)
Objective: To associate the clinical profile of people with stroke to post hospital discharge outcomes. Method: documentary study carried out in a reference unit for stroke in the interior of Brazil’s northeast. The sample consisted of 279 medical records from which data were collected regarding the clynical variables for association with the post discharge outcome. The data were analyzed using bivariate statistics, with the application of statistical tests considering the significance of p <0.05. The study is approved by the Research Ethics Committee of Cariri’s Regional University. Results: the sample had a small male majority with an average age of 69.75 years and admission time greater than four and a half hours (60.6%), interfering in the performance of intravenous thrombolysis (10.4%). The average length of hospital stay was 10.59 days and referral to a rehabilitation service occurred in only 31.5% of cases. The post-discharge outcome was significantly associated with the variables age over 60 years and prolonged of hospital stay. Conclusion: the significant association between the post-discharge outcome and the variables age and length of hospital stay suggests the relationship between cardiovascular risk factors and the clinical severity of the event. Such information is reinforced by the low indication of venous thrombolysis due to the time of admission and referral to rehabilitation services.